Hydropower development impact on household livelihood and economy: a case study in Laos. [Abstract only]. - Milan, Florence M.; Keophosay, Anousith; Senaratna Sellamuttu, Sonali (2013)
The growing regional demand for electricity in Southeast Asia has made Laos a key player in hydropower development since the 1990s. The country's rivers contribute around 35% of the Mekong's flow and have been estimated to have 18,000 MW of exploitable hydropower potential (International Rivers, 2008). While the projects provide revenue for the government of Laos from electricity exports to neighboring countries such as Thailand, Vietnam and China, the hydro boom has not necessarily been good news for Lao villagers affected by these dam constructions. Among others, displacement, land shortages, lack of livelihood opportunities, fisheries losses, flooding and erosion are the main negative impacts that Lao villagers reported in past studies. Thus far, little attention has been given to the impact of hydropower dam constructions on the changes of livelihood activities of affected households. This study contributes to filling this gap by looking into the livelihood changes of villagers residing upstream and downstream of the Nam Gnouang Dam in Laos. After several focus group discussions in the study site, an in-depth livelihood survey was conducted in 2011 covering 110 households living upstream of the Nam Gnouang Dam project and 100 households living immediately below the dam (headpond). Based on households' perceptions, we identify what households considered to be the major positive and negative impacts to their livelihoods brought about by the hydropower development. Using logit/probit regression analysis, we further determine the factors that bring negative or positive changes in the livelihoods of the affected households. A comparative analysis of the effects of the two areas, upstream and headpond, is tested. It is important to investigate the different facets of impact from hydropower dam constructions on affected households. Negative or positive changes in the livelihoods of affected households may depend on the household composition and past livelihood activities. Location of the resettlements may also be an important factor. By taking into account these different factors, we will contribute to the existing literature on hydropower dam interventions. Enhanced, improved or alternative livelihood options with strong adoption potential may well be identified by looking into the determinants of the impact of hydropower dam projects.